Molecular characterization and functional analysis of cytochrome P450-mediated detoxification CYP302A1 gene involved in host plant adaptation in Spodoptera frugieprda - Hafeez, Muhammad; Li, Xiaowei; Chen, Limin; Ullah, Farman; Huang, Jun; Zhang, Zhijun; Zhang, Jinming; Siddiqui, Junaid Ali; Zhou, Shu-xing; Ren, Xiao-yun; Imran, Muhammad; Assiri, Mohammed A.; et al. (Frontiers in Plant Science, 2023)
The fall armyworm (FAW) Spodoptera frugiperda is a destructive and polyphagous pest of many essential food crops including maize and rice. The FAW is challenging to manage, control, or eradicate, because of its polyphagous behavior, transboundary, multiply fast as well as has short life cycle and migrates effortlessly, and lack the diapause development phase. In this study, we evaluated the characterization and functional analysis of the detoxification gene CYP302A1 and how S. frugieprda larvae use a detoxification mechanism to adapt host plants. Results demonstrated that CYP302A1 expression levels were much higher in midgut tissue and the older S. frugiperda larvae. Our current studies revealed the enhanced P450 activity in the midguts of S. frugiperda larvae after exposure to rice plants as compared to corn plants and an artificial diet. Furthermore, higher mortality was observed in pretreated larvae with PBO followed by the exposure of rice plants as compared to the corn plant. The dsRNA of CYP302A1 gene-fed larvae showed lower mRNA expression level in the midgut with greater mortality, reduced larval weight and shorter developmental time followed by the exposure of rice plant as compared to the corn plant and DEPC-water treated plants as a control. These results concluded that the inducible P450 enzyme system and related genes, however, could provide herbivores with an ecological opportunity to adapt to diverse host plants by utilizing secondary compounds present in their host plants.